Identification and characterization of plant growth promoting rhizobacteria indigenous to rhizosphere of sago palm (Metroxylon sagu, Rottb.) - Flonia, Benet (UNIMAS, 2023)
Arising food consumption, climate impacts as well as dwindling arable land have put worries on the agriculture sector that the world's food cupboards may be bare in the coming decades. Metroxylon sagu, Rottb. is one of the underutilized crops which holds high potential to be cultivated for its high starch yield, deemed to strengthen food security especially in Sarawak, Malaysia. However, the quest for boosting M. sagu yields will potentially lead to the future abuse of synthetic agrochemicals and chemical fertilizers. Against this backdrop, biofertilizers have emerged as suitable alternatives to ameliorate sustainable agricultural ecosystems. They are derived from living or dormant microorganisms and one of the foremost candidates in this respect is Plant Growth Promoting Rhizobacteria (PGPR). Despite the fact that much research has been done on PGPR, there are still certain gaps to be addressed, particularly in those related to PGPR indigenous to underutilized crops such as M. sagu, which exposed to stressful environments. Thus, this study was conducted to identify the PGPR indigenous to M. sagu, Rottb. in selected sites at Kuching and Dalat Division of Sarawak State, Malaysia. Given various Plant Growth Promoting (PGP) traits, the study has been approached with hierarchical strategy by screening one of essential nutrients required by plants, the nitrogen. The putative diazotrophic PGPR were initially tested for growth on Burks agar, a nitrogen-free medium. The isolates then were randomly picked and subsequently analyzed for their genetic differences, by Repetitive Extragenic Palindromic (rep-PCR), the (GTG)5 PCR. The banding profiles obtained were analyzed by GelJ_v2.0 software to generate a dendrogram and the isolates were further identified by using 16S rDNA sequencing. These identified isolates then further screened for their PGP traits such as ammonia producer, phosphate solubilizer, IAA and siderophore producer. The superior of identified isolates for their PGP traits was determined by one way ANOVA and they were further ranked based on bonitur scale method. About 54 isolates were isolated as diazotrophic bacteria and about 47 isolates were further subjected to (GTG)5 PCR analysis. Based on the constructed dendrogram, about nine clusters were deduced and nine species were identified. The isolates were deduced to be in the Phyla of Proteobacteria and Firmicutes, consisting of 9 identified species, namely Serratia marcescens, Bacillus sp., Bacillus cereus, Pseudomonas sp., Staphylococcus sciuri, Pseudomonas monteilii, Pseudomonas extremaustralis, Bacillus thuringiensis and Bacillus subtilis. Isolates belonging to genus Bacillus made up 44.4% of the total number of PGPR identified, making it the most prominent genus. All test isolates turned positive for ammonia production. The rhizobacterial isolates of Pseudomonas being the highest phosphate solubilizer (23.08 ± 14.29 mg/L) with no statistically significant difference with other isolates. In IAA production, Pseudomonas. sp. was found to be a significant IAA producer with the presence of tryptophan (26.07 ± 8.53 µg/mL). Production of siderophore was detected in seven out of nine tested isolates. S. sciuri was the highest producer with solubilization index of 1.37 ± 0.06 cm with no statistically significant difference was observed in the amount of IAA produced. According to bonitur scale. Pseudomonas. sp. was determined to be at the top of the scale, followed by S. sciuri, P. monteilii, P. extremaustralis, B. subtilis, B. thuringiensis, Bacillus sp., B. cereus and S. marcescens. Thus, this study implied that the isolates indigenous to the rhizosphere of Metroxtylon sagu, Rottb. possessed PGPR traits. These identified isolates may potentially a good fit as consortium for biofertilizer as well as biocontrol agents which is beneficial for our agriculture industry.